Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1021/bi0020325
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Ionic, Aliphatic, and Aromatic Residues in Membrane−Protein Interactions:  A Surface Plasmon Resonance Study on Phospholipases A2

Abstract: The roles of cationic, aliphatic, and aromatic residues in the membrane association and dissociation of five phospholipases A(2) (PLA(2)), including Asp-49 PLA(2) from the venom of Agkistrodon piscivorus piscivorus, acidic PLA(2) from the venom of Naja naja atra, human group IIa and V PLA(2)s, and the C2 domain of cytosolic PLA(2), were determined by surface plasmon resonance analysis. Cationic interfacial binding residues of A. p. piscivorus PLA(2) (Lys-10) and human group IIa PLA(2) (Arg-7, Lys-10, and Lys-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
203
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(228 citation statements)
references
References 34 publications
(87 reference statements)
23
203
2
Order By: Relevance
“…Concurrently a decrease of k a and an increase of k d were observed, most likely due to the reduced electrostatic interactions and a lesser degree of membrane penetration by the ENTH domain. 19,20 A similar enhancement of the membrane binding affinity upon acidification was seen for the AP180 ANTH domain. We monitored the ANTH domain association with PtdIns(4,5)P 2 -containing vesicles at pH 6.0, 7.4, and 8.0.…”
Section: Affinities Of the Enth And Anth Domains For Ptdins(45)p 2 -supporting
confidence: 59%
See 1 more Smart Citation
“…Concurrently a decrease of k a and an increase of k d were observed, most likely due to the reduced electrostatic interactions and a lesser degree of membrane penetration by the ENTH domain. 19,20 A similar enhancement of the membrane binding affinity upon acidification was seen for the AP180 ANTH domain. We monitored the ANTH domain association with PtdIns(4,5)P 2 -containing vesicles at pH 6.0, 7.4, and 8.0.…”
Section: Affinities Of the Enth And Anth Domains For Ptdins(45)p 2 -supporting
confidence: 59%
“…The association and dissociation phases of sensorgrams were globally fit to a 1:1 Langmuir binding model: protein + (protein binding site on vesicle) ↔ (complex) using BIAevalutation software (Biacore) as described previously. 19 The dissociation constant (K d ) was calculated from the equation…”
Section: Surface Plasmon Resonance (Spr)mentioning
confidence: 99%
“…SPR Measurements-The preparation of vesicle-coated Pioneer L1 sensor chip (Biacore) was described in detail elsewhere (29,30). In control experiments, the sensor chip was coated with vesicles (e.g.…”
Section: Materials-1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholinementioning
confidence: 99%
“…We have shown that the SPR analysis allows direct determination of membrane association (k a ) and dissociation (k d ) rate constants for peripheral proteins (29,31). As summarized in Table I, PKC-␣-C2 has higher affinity (in terms of K d ) for POPC/POPS (7:3) than for POPC/POPG (7:3), and the PS selectivity of PKC-␣-C2 expressed in term of the ratio of 1/K d for POPC/POPS (7:3) to 1/K d for POPC/POPG (7:3) is about 11.…”
Section: Ps Selectivity Of Pkc-␣-c2-mentioning
confidence: 99%
“…A role of basic amino acid residues in plasma membrane targeting has also been found in the C2 domains of phospholipase A2 and protein kinase Ca, for which it was proposed that electric interactions by cationic residues initially bring proteins to anionic membrane surfaces (Stahelin and Cho, 2001;Stahelin et al, 2003). On the basis of these findings, it is postulated that the molecular basis of plasma membrane localization via basic amino acid residues is widely conserved among membrane-targeting proteins in eukaryotes.…”
Section: Discussionmentioning
confidence: 93%